Velocity measurement based on inertial measuring unit - Waru Djuriatno; Eka Maulana; Hasan Hasan; Effendi Dodi Arisandi; Wijono Wijono (Universitas Ahmad Dahlan, 2019)
Vehicles technology have been a priority area of research over the last few decades. With the increasing the use of electronic components in the automotive industry to measure conditions around the vehicle, the focus of automotive technology development is now leading to the development of active technology. Information on the speed of conventional vehicles is generally still obtained based on the rotation of the wheel, but there are weakness in the system that is the diference between wheel and road through vehicle also changes wheel radius of the vehicle due to wind tube air preasure that can change at any time. In this research used Inertial Measuring Unit (IMU) 6 axis (accelerometer and gyroscope) which have been done filtering by using Kalman filter in order to make output sensor value more stable, results obtained at the test of 0 m/s had an RMS error of 0.8696 m/s when elevation is +450; 0.0393 m/s when elevation is 00; and 0.3030 m/s when elevation is -450. this research is expected to be an exploration for the development of a decent system that is suitable to be used as vehicle speed estimator which is as reliable as it is by using an existing speedometer on a ground vehicle generally regardless of slippage and changes in wind capacity on wheels.